Gender identity, culture and ideology in George Eliot’s The Mill on the Floss (Philologia, 2021)
This paper closely examines George Eliot’s response to cultural and ideological perspectives of the Victorian English society based on gender polarisation and her attempt to transcend this segregation in The Mill on the Floss. In terms of culture and ideology, the paper ﬁrst focuses upon the issue of education, which was used by patriarchy as one of ideological state apparatuses to construct and categorise gender identity in the Victorian England. Secondly, the paper deals with a girl’s attempt to ﬁnd out her own voice and way of life beyond what is culturally and ideologically decided for her, yet the paper illustrates how women are crippled, silenced and forced to obey the norms of patriarchal society.
Keywords: patriarchy; culture; education; gender; identity; domesticity; marriage